Sonate pathétique pour le piano : op. 13 composée et dediée à Monsieur le Prince Lichnowski par L. van Beethoven ; edite par J. Moscheles. - Beethoven, Ludwig van, 1770-1827 (composer):::::::::::::::; Moscheles, Ignaz, 1794-1870 (editor)::::::::::::::: (Germany; Braunschweig; J. P. Spehr, 2022)
Early edition of the Piano Sonata no. 8 in C minor, op. 13, published in Braunschweig (Brunswick or Bronswick) by J. P. Spehr and edited by Ignaz Moscheles, including metronome markings. Lacks the decorative title page for the later series that began ca. 1838, which listed the sonatas opp. 2-111.